2022
DOI: 10.1002/jbt.23084
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin exhibits protective effects on in vivo and in vitro asthma models via suppressing TGF‐β1/Smad2/3 and AKT pathways

Abstract: Dioscin is a natural product that possesses protective effects on multiple chronic injuries, but its effects on asthma are not fully understood. Herein, we evaluated its effects on asthmatic mice established by ovalbumin (OVA) sensitization and challenges and further explored the mechanism. Inflammatory cells in bronchoalveolar lavage fluids (BALFs) were analyzed using Diff‐Quik staining. OVA‐specific immunoglobulin E (IgE)/IgG1 in serum and inflammatory cytokines (interleukin 4[IL‐4], IL‐5, IL‐13, and tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Dioscin is a kind of steroidal saponins of Chinese herbal medicine, which has a protective effect on many kinds of chronic injury and antitumor effects (Liu et al, 2022;Shang et al, 2022). Previous evidence had demonstrated that Dioscin upregulates the expression of Cx43 and improves gap junction communication in B16 cells (Kou et al, 2017;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dioscin is a kind of steroidal saponins of Chinese herbal medicine, which has a protective effect on many kinds of chronic injury and antitumor effects (Liu et al, 2022;Shang et al, 2022). Previous evidence had demonstrated that Dioscin upregulates the expression of Cx43 and improves gap junction communication in B16 cells (Kou et al, 2017;Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dioscin, a kind of steroidal saponins extracted from some medicinal plants, has multiple medicinal efects including anti-infammatory and anticancer efects. It was reported that dioscin restrained chronic asthmatic mice by altering TGF-β1/Smad2/3 and Akt signalling pathways and reversed TGF-β1-induced EMT in 16HBE cells [63].…”
Section: Te Efect Of Specifc Herbal Compounds On Emtmentioning
confidence: 98%
“…Icariin [61] OVA-induced asthma in mice MAPK/Erk Nodakenin [62] OVA-induced asthma in mice IL-4, IL-5, IL-13, MMP2/9, and NF-κB Dioscin [63] OVA-induced asthma in mice TGF-induced HBE16 TGF-β/Smad…”
Section: Te Efect Of Specifc Herbal Compounds On Emtmentioning
confidence: 99%
“…Numerous research has suggested that dioscin has broad-spectrum pharmacological activities, such as anti-oxidative, anti-fibrosis, anti-proliferation, anti-allergic, anti-viral, anti-inflammation, anti-fungal, immunoregulation, anti-hyperuricemia, anti-aging, pro-autophagic, anti-thrombotic, and cholesterol-lowering effects and possesses fewer side effects compared with the drugs with the same effect in current clinical application relatively speaking 12 - 14 . Dioscin also provided obvious protective effects on various metabolic disorders, such as fatty acid metabolism and the damage of organs, including the kidney, liver, lung, and heart 15 - 17 . Furthermore, dioscin reduced chemoresistance 18 and regulated M1 macrophage polarization and differentiation of myeloid-derived suppressor cells 19 .…”
Section: Introductionmentioning
confidence: 99%